Ex-situ Morphological and Morphometric Studies of the Testis In the West African Dwarf Buck GoatEx-situ Morphological and Morphometric Studies of the Testis In the West African Dwarf Buck Goat - Lukman Oladimeji Raji; Oluwatoyin Oluwasola Ajala (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to document ex-situ morphological and morphometric characteristics of the testis in the West African Dwarf (WAD) buck goat. For this aim, 24 post pubertal WAD buck testes were collected at the Ipata Abattoir in Ilorin, Kwara state, Nigeria. Gross morphologic results revealed that WAD testis was ellipsoidal in shape with 2 borders (free and attached), margins (medial and lateral) and similar surfaces (ventral and dorsal). The surfaces were covered by an outer tunica vaginalis and a deep tunica albuginea. Histomorphology showed the testis comprised mostly of rounded and some irregularly shaped seminiferous tubules (ST). Each ST was lined by a basement membrane and a layer of germinal epithelium with lumen filled with spermatozoa surrounded by an adluminal space. Gross morphometric results showed that there were no significant differences in the weight, length, width and height of the right and left testis. Also in the volumes of testes obtained by water displacement method and using the prolate ellipsoid formula. There was a strong correlation between the weights and volumes of testes obtained using these methods. There were significant differences between the volumes of testes obtained by using the prolate spheroid and Lambert formulae, when compared with those obtained by water displacement method respectively. But there was no significant difference in testicular volume obtained by the prolate ellipsoid formula and the water displacement method. Histomorphometric results revealed no significant differences in the seminiferous tubular diameter, seminiferous luminal diameter and germinal epithelia height of the right and left testes respectively. The morphological and morphometric data highlighted in this study would be useful in comparative regional anatomy and researches on the testis of these valuable breed of goats.